Contemporary political philosophy an anthology - Goodin, Robert E.; Pettit, Philip 1945- (Blackwell philosophy anthologies, 2019)
"The essays contained in this collection represent what seem to us to be canonical texts in contemporary political philosophy. But they only represent the contemporary canon, they do not exhaust it. Although this collection is two or perhaps three times the size of most, we nevertheless found that we had space for only a sample of the very many more texts and topics that we would like to have included.The collection is deliberately designed as a companion to our earlier Companion to Contemporary Political Philosophy (Oxford: Wiley-Blackwell, 1993; 2nd edition, 2012). We attempted to retain something of the same flavor in this collection, much the same scope of substantive concerns and much the same diversity of analytic styles. Inevitably, though, there is so much more surveyed in the Companion's many chapters than can be reprinted here. Interested readers are referred back to the Companion not only to situate the texts in the present collection but also for further readings and whole other sets of concerns"--